Effect of the Dengue Ranger Educational Board Game on Elementary School Students' Knowledge of Aedes aegypti Breeding Sites and 3M-Plus Practices - Pratama, Putu Ari Wirya; Wiweko, Adnanto; Parwata, Wayan Sulaksmana Sandhi; Karuniawaty, Titi Pambudi (Jurnal Biologi Tropis, 2026)
Dengue hemorrhagic fever (DHF) remains a major public health problem, requiring effective mosquito breeding site control through the 3M-Plus program involving community participation, including elementary school students. This study aimed to compare the effectiveness of the Dengue Ranger educational board game and the Ministry of Health leaflet in improving students' knowledge of Aedes aegypti breeding sites and 3M-Plus practices. A quasi-experimental study with a non-equivalent control group design was conducted among 213 students from grades 3–6 at SD Negeri 37 Ampenan. Participants were selected using cluster sampling and assigned to the board game group (n = 108) or the leaflet group (n = 105). Knowledge was assessed using a validated questionnaire before the intervention, immediately after, and seven days later. Data were analyzed using the Wilcoxon signed-rank test and Mann–Whitney U test. Knowledge scores increased significantly in both groups (p < 0.05). The mean score increased from 10.50 to 12.44 in the board game group and from 10.79 to 12.05 in the leaflet group. The board game demonstrated significantly greater improvement than the leaflet (p < 0.05). However, no significant difference was observed in knowledge retention after seven days (p > 0.05). These findings indicate that the Dengue Ranger educational board game is more effective than leaflets in improving elementary school students' knowledge of Aedes aegypti breeding sites and 3M-Plus practices, while both media provide comparable short-term knowledge retention.